A Study of Diplomatic Protocol and Etiquette
XV, 281 p. 21 illus., 10 illus. in color.
Keywords: This book, with its focus on the study of diplomatic protocol and etiquette, collects high-quality papers written by scholars in diplomatic protocol from nine countries, including US, UK, Russia, Japan, Canada, Netherlands, India and China. As a result of in-depth international academic cooperation, it explores diplomatic protocol from three dimensions of theory, practice and country-specific and has the characteristics of internationality and nationality. From a global perspective, it is the first time that experts from so many countries work together in diplomatic protocol which makes this book present a more comprehensive and diverse overview. This book, as an effort made to enhance understanding among different cultures and facilitate the harmonious coexistence of people across the world, is remarkably helpful for promoting the research of diplomatic protocol and etiquette, exploring the true connotation of protocol and etiquette, and improvingits practicality in realities. .